2023
DOI: 10.1002/pca.3254
|View full text |Cite
|
Sign up to set email alerts
|

Identifying druggable targets from active constituents of Azadirachta indica A. Juss. for non‐small cell lung cancer using network pharmacology and validation through molecular docking

Abstract: IntroductionAzadirachta indica A. Juss. is a well‐known medicinal plant that has been used traditionally to cure various ailments in every corner of the globe. There are many in vitro and in vivo experimental evidences in connection with the bioactivity of the extracts of this plant. Lung cancer is the deadliest form of cancer and contributes to the most cancer related deaths. The mode of action of anticancer components of this plant is still to be established explicitly.ObjectiveThe objective of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…44 It is noteworthy that nimbolide, a covalent recruiter of the E3 ubiquitin ligase RNF114, can be used for targeted protein degradation that can be exploited for degrading therapeutically important targets, such as the BCR-ABL fusion oncogene. 161 Recently, Nath et al 162 identified EGFR, BRAF, and PIK3CA as druggable targets of neem for NSCLC using network pharmacology. Validation by molecular docking and absorption, distribution, metabolism, excretion, and toxicity (ADMET) profiling revealed that desacetylnimbin, nimbandiol, nimbin, nimbinene, nimbolide, salannin, and vepinin are the most active neem limonoids against NSCLC.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…44 It is noteworthy that nimbolide, a covalent recruiter of the E3 ubiquitin ligase RNF114, can be used for targeted protein degradation that can be exploited for degrading therapeutically important targets, such as the BCR-ABL fusion oncogene. 161 Recently, Nath et al 162 identified EGFR, BRAF, and PIK3CA as druggable targets of neem for NSCLC using network pharmacology. Validation by molecular docking and absorption, distribution, metabolism, excretion, and toxicity (ADMET) profiling revealed that desacetylnimbin, nimbandiol, nimbin, nimbinene, nimbolide, salannin, and vepinin are the most active neem limonoids against NSCLC.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%